2010
DOI: 10.1016/j.amepre.2010.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Determinants of Outdoor Play in Children

Abstract: Neighborhood social cohesion was related to outdoor play among children of different age and gender, which makes it a promising point of action for policy development. Policies aimed at improving physical neighborhood characteristics in relation to outdoor play should take into account age and gender of the target population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
118
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 105 publications
(135 citation statements)
references
References 41 publications
8
118
3
3
Order By: Relevance
“…Most of these studies examined outdoor play and/or physical activity. Overall, outdoor play and physical activity in the early years was positively associated with neighborhood greenness (Lovasi et al, 2011;Grigsby-Toussaint et al, 2011), access to nature (Fjortoft and Sageie, 2000), green public open space (Taylor et al, 1998;Aarts et al, 2010), parks (Roemmich et al, 2006) and playgrounds (Quigg et al, 2011;Sallis et al, 1993). In an observational study of 262 children aged 3-12 years, levels of play in barren spaces were about half as much as in spaces with trees and grass (Taylor et al, 1998).…”
Section: Green Spacesmentioning
confidence: 95%
See 3 more Smart Citations
“…Most of these studies examined outdoor play and/or physical activity. Overall, outdoor play and physical activity in the early years was positively associated with neighborhood greenness (Lovasi et al, 2011;Grigsby-Toussaint et al, 2011), access to nature (Fjortoft and Sageie, 2000), green public open space (Taylor et al, 1998;Aarts et al, 2010), parks (Roemmich et al, 2006) and playgrounds (Quigg et al, 2011;Sallis et al, 1993). In an observational study of 262 children aged 3-12 years, levels of play in barren spaces were about half as much as in spaces with trees and grass (Taylor et al, 1998).…”
Section: Green Spacesmentioning
confidence: 95%
“…Only three studies examined this relationship (Aarts et al, 2010;Barnett et al, 2012;Marino et al, 2012). One study found that not having a garden at home where children can play resulted in more outdoor play in 4-6 year old Dutch girls (Aarts et al, 2010). In contrast a small Australian study identified that the home outdoor space may be important for providing equipment for facilitating play and physical activity and developing motor skills (Barnett et al, 2012).…”
Section: Outdoor Home Areamentioning
confidence: 96%
See 2 more Smart Citations
“…Most of these use questionnaire methods (e.g. Aarts et al 2010;Bringolf-Isler et al 2010) or diaries (Wen et al 2009), even though the behaviour lends itself to ethological study. Although this literature has established that outdoor play behaviour may be inversely associated with socioeconomic position (Ellaway et al 2007;Aarts et al 2010), this finding has not been linked to social gradients in parenting strategies more generally.…”
Section: Introductionmentioning
confidence: 99%